Socioeconomic and clinical-epidemiological profile of people attended in an outpatient clinic for complex wounds - Cavalcante, Viviane Mamede Vasconcelos (2020)
Objective: to characterize the socioeconomic and clinical-epidemiological profile of people attended in an outpatient clinic specialized in complex wounds. Methods: cross-sectional study with 69 people with wounds, through the application of a questionnaire. Data analyzed using descriptive and analytical statistics. Results: most participants were male (55.1%), above 60 years old (55.1%), married (40.6%), income from one to three minimum wages (69.6%). Regarding clinical aspects, 50 (72.4%) had the injury for more than six months, 32 (46.4%) had a relative responsible wound dressing, 44 (63.8%) did not have difficulties in wound dressing. Regarding how long they had the wound, pain and arterial disease were statistically significant (p=0.042; p=0.026). Conclusion: most participants were male and above 60 years old. Pain and the presence of arterial diseases were significant with regards to people with chronic wounds.